ASPEK TEKNOLOGI DAN EKONOMI PEMBANGUNAN PABRIK PENGOLAHAN BIJIH BESI MENJADI PRODUK BAJA DI INDONESIA[Technological and Economical Aspects of The Intallation of Iron Ore Processing Plant to Produce Steel In Indonesia.] - Zulhan, Zulfiadi (Jurnal Metalurgi, 2013)
Raw material for steel production in Indonesia is still imported either in the form of iron ore or steel scrap. The utilization of domestic iron ore to produce sponge iron might substitute steel scrap as raw material for EAF-based steelmaking. Indonesian iron ore can be classified into primary iron ore (hematite and magnetite), lateritic iron ore and iron sand. Lateritic iron ore is more dominant in Indonesia, therefore the suitable technology and process route shall be studied in order to obtain an optimum and efficient process as well as to produce high quality steel. The domestic price of natural gas tends to increase in the following years, therefore coal based direct reduction technology (e.g. rotary kiln) or blast furnace for high production capacity should be installed. The scarcity of domestic coking coal fo coke production is the limitation by the application of blast furnace technology. The comparison of capex and opex of blast furnace and rotary kiln iron making is described in this paper. The steel production cost using rotary kiln – electric arc furnace route or blast furnace – basic oxygen furnace route is nearly the same (around 500 USD/ton).